Genetic diversity in a collection of apple (Malus x domestica Borkh.) cultivars as revealed by RAPD markers - Garkava-Gustavsson, L.; Nybom, H. (International Journal of Horticultural Science, 2007)
A collection of 151 apple cultivars was investigated with 7 RAPD primers generating 71 informative bands, to evaluate genetic variability and relatedness. All cultivars presumably derived through genetic recombination were distinguished whereas identical DNA profiles indicated that some cultivars had arisen as sports. A cluster analysis and a PCO did not reveal any distinct geographic patterns, but there was a weak tendency for Swedish and foreign cultivars to differentiate.. Many cultivars however clustered together with either one of their parents or with siblings. Overall genetic diversity among the 151 cultivars was estimated with Nei's diversity index (H), 0.269, and with Shannon's index (H'), 0.594. The cultivars were also analysed in six groups, according to time of origination and country of origin, with an average H = 0.262 and H' = 0.546. No major differences in genetic diversity were observed over time or space, although the group with recent, foreign cultivars had the lowest diversity (FL = 0.235, H' = 0.493). Comparison between the entire material and a subset with 94 mandate cultivars chosen for preservation in Sweden, showed similar genetic diversity: HFN.rj1E = 0.268, frE,NTIRE, = 0.593 and HMANDATE = 0.263, WMANDATE = 0.575. No major differences in band frequencies were observed between these two sets, but 5 RAPD bands were missing in the set with mandate cultivars.